Ruthenium-Catalyzed [2+2+2] Bis-Homo-Diels–Alder Cycloadditions of 1,5-Cyclooctadiene with Alkynyl Phosphonates - Petko, Dina; Pounder, Austin; Tam, William (Synthesis, 2019)
The ruthenium-catalyzed [2+2+2] bis-homo-Diels–Alder cycloaddition between 1,5-cyclooctadiene and alkynyl phosphonates was investigated. Various alkynyl phosphonate moieties were found to be compatible with the cycloaddition to give the tricyclo[4.2.2.02,5]dec-7-ene tricyclic compounds in yields of 46–97%.
Keywords: 1,5-cyclooctadiene; bis-homo-Diels–Alder reaction; cycloaddition; ruthenium-catalyzed; alkynyl phosphonate